KOMPARASI NILAI EKONOMI AIR IRIGASI DARI DAERAH ALIRAN SUNGAI BERHUTAN DAN TIDAK BERHUTAN - Purwanto Purwanto (Jurnal Ilmu Lingkungan, 2019)
Many forest areas in Indonesia are converted to other uses. This will impact on the hydrological conditions and the economic value of the water yield. This research applied unit analysis of Sub watersheds, with and without forest cover, Sub DAS Banjaran (forested) and Sub CAS Cangkok (not forested). Desk analysis was conducted to know land use, collecting rainfall data, instantaneous debit measurement to know the discharge of both rivers during the dry season, survey of 15 farmers using irrigation water from Sub watershed of Banjaran and 15 peasants who use irrigation water from Cangkok Sub watershed. Farmers were interviewed about the factors of production and production of rice crops to determine the economic value of water from the two sub watersheds. The results of the study show that: 1). rainfall in Baturraden is quite high (4,302 mm) but for May, July, August and September deficits for rice crops, 2). The forested sub-watershed in Baturraden is better able to regulate the water system than the non-forested sub-watershed, either quality, quantity or continuity, 3). The economic value of water for irrigation from the forested sub-watershed is Rp. 1,270,-/m3 whereas from non-forested sub-watersheds Rp. 373.5,-/m3, and 4). The economic value of water from a forested sub-watershed is Rp. 7,792,720,-/ha/year while those from non-forested sub-watersheds Rp. 2,291,796,-/ha/year. The existence of Baturraden forest is very important to the watershed ecosystem. Forested watershed was a higher economic value of water than non-forested ones so it must be conserved by involving the water user communities.